Evaluation of Artificial Lighting in the Hospitals of Tehran University of Medical Sciences and the Satisfaction of the Medical Staff in 1400 - Farahnaz KHAJEHNASIRI; Seyed Abolfazl ZAKERIAN; Zahra Sadat MOUSAVI FARD (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: One of the important factors in providing safety and preventing stress in medical staff and patients referred to hospitals at night is the provision of standard lighting in the hospital. This study aims to determine the mean score of area artificial lighting and compare it with the standard in the hospitals of Tehran University of Medical Sciences and the satisfaction of the medical staff. Methods: In this cross-sectional study (descriptive-analytical), the intensity of general lighting at night was checked and compared with standard values based on the proposed models of the North American Society of Lighting Engineers using a lux meter, in Sina, Imam Khomeini, and Shariati hospitals of Tehran University of Medical Sciences. The satisfaction of the emergency medical staff with the lighting of the hospital area was assessed by a short researcher-made questionnaire. Descriptive and analytical statistics of the data were provided by SPSS software, version 22. Results: Based on the results of this study, the mean and standard deviation of lighting in Sina, Imam Khomeini, and Shariati hospitals were 33.12 ± 47.84, 24.67 ± 54.51, and 6.73 ± 10.87, respectively. The results showed that 55.4% of night shift staff were not satisfied with the area lighting. The mean score of lighting of the general hospital area (19.19 lux) was significantly different from the standard of hospital area lighting (50 lux) (PV = 0.000). Conclusion: The results of this study showed that the mean score lighting of the hospitals area was significantly lower than the lighting standard and the need to improve lighting systems is emphasized.